Inverse Identification of Composite Material Properties by using a Two-Stage Fourier Method - Tam, Jun Hui; Ong, Zhi Chao; Ismail, Zubaidah; Ang, Bee Chin; Khoo, Shin Yee (Springer, 2018)
This study presents a feasible identification method for composite materials that adopts the combined use of the Fourier method, a weighted least squares method and the mode shape error function. The deflection shape function of the plate structure is defined in terms of 2D Fourier cosine series which is supplemented with several one-dimensional additional terms to accommodate general boundary conditions. The derivatives of mode shape with respect to the flexural rigidity are derived and computed from the model’s displacement function. A difference exists in the means of obtaining the mode shape derivatives between the present approach and the commonly used finite element model updating method. This research proposes a two-stage identification approach, in which the natural frequency error function is utilised in stage 1. In stage 2, the mode shape error function is used, which is proven vital in improving the accuracy of the in-plane shear modulus and Poisson’s ratio by at most 13%.